Tıme Schedule Analysıs Of Green House Project Batam - Radha Purnamasari; Usmanul Hayadi Umar (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2022)
Practical work is a compulsory subject taken by students. Practical work carried out by the author aims to analyze the time schedule in the initial plan for the Batam green house development project. Practical work carried out by the author starts from October 25, 2021 until January 25, 2022. In collecting practical work data, the author uses observation methods and instruments. The author collects work data directly from the project field, so that the results of the analysis can be used to compare the initial plan and the realization time of the time schedule in the field. This aims to find out whether there is a delay in the project. After doing practical work, the final result obtained by the author is a delay in the time schedule from the original plan. The project was delayed by five weeks. One of the factors causing delays is the weather.